High-Frequency rTMS of the Motor Cortex Modulates Cerebellar and Widespread Activity as Revealed by SVM - Wang, Jue; Deng, Xin-Ping; Wu, Yun-Ying; Li, Xiao-Long; Feng, Zi-Jian; Wang, Hong-Xiao; Jing, Ying; Zhao, Na; Zang, Yu-Feng; Zhang, Jian (Frontiers in Neuroscience, 2020)
Functional magnetic resonance imaging (fMRI) studies have shown that the effect of repetitive transcranial magnetic stimulation (rTMS) can induce changes in remote brain regions. In the stimulated regions, low-frequency (≤1 Hz) rTMS induces inhibitory effects, while high frequency (≥5 Hz) stimulation induces excitatory effects. However, these stereotypical effects arising from low- and high-frequency stimulation are based on measurements of motor evoked potentials (MEPs) induced by pulsed stimulation. To test the effects of rTMS on remote brain regions, the current study recruited 31 young healthy adults who participated in 3 rTMS sessions (10 Hz high-frequency, 1 Hz low-frequency, and Sham) on 3 separate days. The stimulation target was based on individual fMRI activation in the motor cortex evoked by a finger movement task. Pre- and post-rTMS resting-state fMRI (RS-fMRI) were acquired. Regional homogeneity (ReHo) and degree centrality (DC) were calculated to measure the local and global connectivity, respectively. Compared with the sham session, high-frequency (10 Hz) rTMS significantly increased ReHo and DC in the right cerebellum, while low frequency (1 Hz) stimulation did not significantly alter ReHo or DC. Then, using a newly developed PAIR support vector machine (SVM) method, we achieved accuracy of 93.18-97.24% by split-half validation for pair-wise comparisons between conditions for ReHo or DC. While the univariate analyses suggest that high-frequency rTMS of the left motor cortex could affect distant brain activity in the right cerebellum, the multivariate SVM results suggest that both high- and low-frequency rTMS significantly modulated widespread brain activity. The current findings are useful for increasing the understanding of the mechanisms of rTMS, as well as guiding precise individualized rTMS treatment of movement disorders.